Comparison of Pediatric Burn Wound Colonization and the Surrounding Environment. Issue 2 (2nd April 2016) - Fore, Sara E.; Munchel, Emily C.; Goldstein, Seth; Mills, Joanne; Vanderwagen, Sarah; Stewart, Dylan; Colombani, Paul
ABSTRACT: There are wide ranging practices in barrier isolation standards for pediatric burn patients. The benefits of barrier isolation for burn patients have not been clearly shown through scientific study. Research has shown that patients with a total body surface area (TBSA) burn larger than 30% are more likely to require special precautions, however to date there has been no study that delineates the effect of isolation and precaution techniques on wound infection in pediatric patients with burns less than 20% TBSA. The aim of this research was to determine if small burn wounds (less than 20% TBSA) are colonized with bacterial growth and if that same bacteria is contaminating the patient's surrounding environment, therefore requiring barrier isolation. The goals of this study were: to determine the colonization rates in burn wounds in our hospital setting, to decrease patient and family anxiety related to barrier isolation, and to decrease unnecessary use of hospital resources, e.g., isolation attire and time. Results from this research study led to a change in hospital policy.